Meta-Analysis: The Effectiveness of Web-Based Health Promotion Interventions on Vegetable Consumption in Children - Sinar Perdana Putra; Yulia Lanti Retno Dewi; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Consuming healthy food throughout life helps prevent malnutrition in all forms of various diseases. In the first 2 years of a child's life, optimal nutrition fosters healthy growth. Vegetables and fruit are food sources that contain many nutrients that humans must consume at every meal. EHealth is playing an increasingly large role in life and the internet has great potential to be a source of low cost and effective health promotion interventions.Subjects and Method: This study was a meta-analysis of a number of Randomized Controlled Trial study designs. The articles used in this study were obtained from several databases including PubMed, Google Scholar, and Springer Link. The articles used in this research are those published from 2010-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. The population in the study was children aged 2 to 12 years old with an intervention in the form of web-based health promotion, comparison, which was not given a web outcome-based health promotion intervention in the form of vegetables consumption. The keywords for finding articles are as follows: